A Review on Cosmetic Formulations and Physicochemical Characteristics of Emollient and Day Cream Using Vegetable Based-Wax Ester - Nooratiqah Azmi; Salina Mat Radzi; Nur Amalina Mohd Amin; Maryam Mohamed Rehan (USIM Press, 2024)
Vol. 8 No. 2 (2022)